Perspectives of man submitted to penectomy / Perspectivas do homem submetido à penectomia - Luiz Carlos Veiga Madriaga; Silvia Sant'Anna Silva de Souza; Gicélia Lombardo Pereira; Beatriz Gerbassi Costa Aguiar (Universidade Federal do Estado do Rio de Janeiro, 2020)
Objective: this article aims to describe the perspectives of patient submitted submitted to penectomy and to know the perspectives of this patient after the penectomy. Methods: its a case study realized in a federal hospital of Rio de Janeiro city with two patients who were admitted to the hospital during 2017 and underwent to penectomy surgery.  The data collection was realized during 2018 with a semi-structured interview. The participants were protected by the ethics principles established by the resolution 466/ 2012 of the National Health Council and this study was approved under the number 2.769.381. Results: it was found that penectomy in this case studies was the only therapy. Thereby, the desire of being among their family and to extend their life was determinants to adhere the therapy. Conclusion: it was concluded that even with the changes in their body, the penectomy was realized to extend the life.